Ovarian papillary carcinoma in a Mongolian gerbil (Meriones unguiculatus) - Claro, Ana Julia Tonetti [UNESP]; da Silva, Gustavo Bauer Costa; Maia, Suellen Rodrigues [UNESP]; Moraes, Reiner Silveira de [UNESP]; de Azevedo, Maria Gabriela Picelli [UNESP]; Geraldes, Silvano Salgueiro [UNESP]; Melchert, Alessandra [UNESP]; Guimarães-Okamoto, Priscylla Tatiana Chalfun [UNESP] (Brazilian Journal of Veterinary Pathology, 2023)
Neoplasms are among the most impacting disease diagnoses in veterinary medicine and have become increasingly common due to the greater longevity of animals as living conditions improved. The Mongolian gerbil is a small rodent species that has become popular recently. In these animals, the occurrence of neoplastic processes is relatively common, mainly tumors of the ventral gland in males and ovarian tumors in females. This work aims to report an ovarian tumor in a Mongolian gerbil Mer-iones unguiculatus Milne-Edwards 1867 (Rodentia, Muridae). At the initial presentation, the animal had dyspnea, prostration, and increased abdominal volume in the topography of the right ovary of approximately 2 cm. The animal was submitted to exploratory laparotomy because of the emergency nature of the case and the owners’ refusal of additional exams due to financial restrictions. Thus, an ovariohysterectomy was performed, followed by a histopathological examination. The histopathology revealed an ovarian papillary carcinoma affecting both ovaries and cystic endometrial hyperplasia. With surgical removal and drainage of the thoracic fluid, the animal showed good recovery, with general improvement and return to regular activity, with a life expectancy of two years. Currently, the demand for specialized veterinarians for unconventional pets is increasing. This condition allows owners to raise their animals more properly, favoring greater longevity. Knowledge about the prevalence and incidence of diseases in different species is of enormous relevance in establishing the appropriate therapy, improving life quality, and increasing life expectancy in animals’ lives.
Keywords: female reproductive system; rodent; tumor